European Politics and Historical Revisionism - Deletić, Zdravko (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The radical change of politics and ideology in the post-communist states in the Yugoslav area caused a revaluation of national histories. The production of desirable history has the political support of the current authorities in the states that emerged from the break-up of Yugoslavia. The features of revaluing the past and writing desirable history are: anti-communism, anti-Yugoslavism and radical nationalism. At the same time, the engaged attitude towards anti-fascism as a national phenomenon is evident. Partisan anti-fascism is diminished or denied, the partisan movement and communist ideology are criminalized by insisting on real and imagined crimes, retaliation and repression against ideological opponents. Communism is completely declared a totalitarianism and a nationally harmful ideology. On the other hand, the ideology and practice of the subjects of collaboration are being relativized and efforts are being made to relativize responsibility, to present collaboration as a national need. Through a series of resolutions and recommendations from 1996 to 2019, the Parliamentary Assembly of the Council of Europe obliged the former socialist states to reconsider their past, to "dismantle" communism and remove the consequences of communist rule, to rehabilitate victims of punishment for ideological conflicts. Everything is at the level of theory and anti-communist ideology. Procedures are not standardized, as the re-examination of the communist-socialist past should be performed by the proposed subjects who can competently revise history and eliminate the consequences of totalitarian rule. History is being re-examined by whoever wants it, and rehabilitation without guilt is being done by local courts. There are no clear statements that revisionist practice is conditioned by European resolutions and declarations, but the character and content of revisionist journalism is in line with the adopted requirements.